PENGARUH PEMAHAMAN WAJIB PAJAK, KESADARAN WAJIB PAJAK, DAN PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK BUMI DAN BANGUNAN - Imam Oktafiyanto; Dewi Kusuma Wardani (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2015)
The purpose of this study was to determine the affect of understanding the taxpayer, the taxpayer awareness, and services tax authorities on tax compliance and building earth. This research was conducted in the department of Regional Tax and Financial Management of Yogyakarta. Data Collected by using a questionnaire. Tecnical analysis of the data used is multiple linier regression technique. Based on the analysis that has beeb done, it can be seen that the understanding of the taxpayer, the taxpayer awarenness, and service tax authoroties on tax compliance affect the land and building. Keywords: Understanding taxpayer, taxpayer Awareness, Service tax authorities andTaxpayer Compliance.